Novel conventional and chelating anion exchange resins with amino ligands for sorption of silver. Issue 12 (12th August 2020) - Pilśniak-Rabiega, Magdalena; Wejman, Katarzyna; Wolska, Joanna
ABSTRACT: The polymeric resins containing diethylenetriamine, tetraethylenepentamine, 2-(diethylamino)ethanol, 1-methylimidazole, and 1, 2-dimethylimidazole ligands have been synthesized from vinylbenzyl chloride-divinylbenzene copolymers and used in the removal of Ag(I) from chloride solution. The best Ag(I) sorption was reached in the case of 1-methylimidazole resin. Resins retain their capacity towards Ag(I) in five consecutive sorption/desorption cycles. The resins with imidazole ligands were highly selective for Ag(I) from synthetic chloride solution and they did not sorb chloride complexes of Cu(II). Additionally, the recovery of Ag(I) was tested from real chloride solution coming from leaching of the copper concentrate from Lubin Concentrator (KGHM Polska Miedź S.A.).